The Correlation Between Stress Levels And Self-Care Behavior of Hipertensive Elderly - Wimar Anugrah Romadhon; Suprajitno Suprajitno; Yeni Kartika Sari; RR Dewi Rahmawaty (Jurnal Kesehatan Prima, 2022)
Hypertension in the elderly becomes a serious problem if not treated as early as possible and will cause complications. The problem that often occurs in hipertensive elderly is have problems with suboptimal self-care behavior. This is influenced by the level of stress that the elderly have to change their optimal self-care behavior. The purpose of this study was to determine the correlation between stress levels and self-care behavior in hipertensive elderly. Descriptive correlation was used in this study with a cross sectional approach and the sample obtained was 252 of hipertensive elderly in the Surabaya Public Health Center Area with a cluster random sampling. Data were analyzed using Spearman Rho test. The hipertensive elderly had a stress level of 0.8% in the severe category and 46.8% in the moderate category and 52.4% in the mild category. The elderly also have self-care behavior of 31.7% in the low category, 39.3% in the sufficient category, 29% in the good category. This study shows a significant correlation between stress levels and self-care behavior with a value of p = 0.000  (<0.05) and the coefficient correlation had a fairly strong relationship with a negative value of -0.384. This study shows that there is a correlation between stress levels and self-care behavior in hypertensive elderly and a negative value indicates that if the elderly with stress is getting heavier or higher, their self-care behavior tends to be bad or down. Nurses must understand that stress levels something that needs to be studied in behavioral changes in hipertensive elderly to provide comfort in carrying out self-care behavior